(untitled) (Nigerian Journal of Physiological Sciences, 2025)
D-Ribose-L-Cysteine (Riboceine)- an antioxidant supplement that may help to raise the glutathione levels by acting as a precursor for glutathione biosynthesis in biological systems. Effect of riboceine (Rb) on sodium arsenite (SA) induced hepatorenal toxicity was investigated in rats. Four groups (A-D) (six per group) were treated thus: Group A (water and normal diet only); while Group B (SA at 5 mg/kg body weight); Group C (riboceine at 10 mg/kg body weight) and Group D (riboceine and SA). The exposure to test substances lasted for a total of 14 days in each case in which pre-treatment was done with riboceine. Exposure to SA triggered a significant reduction in the entire weight and relative organ weight, increase in ALT (alanine aminotransferase), AST (aspartate aminotransferase), ALP (alkaline phosphatase) activities, decrease in liver total protein and increase in serum levels of urea and creatinine. Furthermore, SA caused a significant reduction in GSH (glutathione) level and CAT (Catalase) activity, while the LPO (lipid peroxidation) and NO (nitric oxide) levels were significantly increased. Pre-treatment with riboceine, restored the levels of the aforementioned parameters. Riboceine also promote restoration of hepatocytes and renal cells integrity. Findings from this study reaffirm the hepatorenal toxicities of sodium arsenite and show the protective role of riboceine against SA-induced toxicities. Protective effects of riboceine may be via the enhancement of the level of glutathione, a natural scavenger of free radicals.